Symposium 4: Community Dimensions of Learning Object Repositories - Margaryan, Anoush; Littlejohn, Allison; Nicol, David (Proceedings of the International Conference on Networked Learning, 2006)
This paper outlines some enablers and barriers in the use of learning object repositories (LORs) to support learning within a range of communities. Key dimensions of use of LORs as well as relationships between LORs and the learning communities that they aim to support are discussed. The LORs and communities analysed in the paper are SIESWE Learning Exchange (formerly Stor Curam), JORUM, IVIMEDS, and DIDET. Guided by the Activity Theory perspective, the LORs and the communities are analysed as sociocultural activity systems. Based on this analysis, some initial barriers and enablers for the use of LORs to support learning are outlined and implications for the future use of LORs are discussed.